Conflicting Perspectives on Humanitarian Intervention: In Light of the Darfur Crisis - Issak, Samuel Aron (Journal of Humanities and Social Sciences Studies, 2021)
This paper discusses the US and China’s response to the Darfur crisis in order to examine the underlying conflicting perspectives on the legitimacy of humanitarian intervention. The findings show that the US and China characterized the Darfur crisis differently. For the US the level of violence in Darfur was genocide; thus, robust humanitarian intervention was required to stop it. On the other hand, China described the situation as a crisis, but not genocide. Therefore, addressing it requires a peace process rather than humanitarian intervention. This is a clear indication of the conflicting perspectives that exist around the principle of humanitarian intervention. The reason is that national interest rather than humanitarian consideration seems to dictate their response to the Darfur crisis.